Changes in gut microbiota following supplementation with chitosan in adolescents with overweight or obesity: a randomized, double-blind clinical trial - Somaye Fatahi; Mohammad Hassan Sohouli; Koroush Vahidshahi; Pejman Rohani; Majid Safa; Masoud Salehi; Mihnea-Alexandru Găman; Farzad Shidfar (Diabetology & Metabolic Syndrome)
Abstract Background Overweight and obesity have been associated with an altered intestinal microbiome. Recent investigations have demonstrated that fiber supplementation, including chitosan, can exert beneficial and protective effects on the composition of gut microbiota in humans diagnosed with overweight/obesity. However, there is still a great deal of heated debate regarding the impact of chitosan supplementation in overweight and obese adolescents. Therefore, the aim of this study is to clarify the effects of chitosan administration on the composition of the gut microbiome in overweight and obese adolescents. Methods and analysis Sixty-four overweight and obese adolescents were subjected to supplementation with 3 g of chitosan for 12 weeks. Anthropometric indices and physical activity were measured at the beginning and at the end of the intervention. After DNA extraction and purification, the quantity of bacteria in the patients’ stool samples was determined by real-time polymerase chain reaction (PCR). The RCT was registered on the Iranian Registry of Clinical Trials ( www.irct.ir ) website (IRCT20091114002709 N57; registration date: 2021 - 06 - 20). Results Individuals who received chitosan supplementation experienced a significant decrease in the BMI z-score (P < 0.001). Administration of chitosan led to notable significant decrease in the Firmicutes (P < 0.001) populations and the ratio of Firmicutes to Bacteroidetes (P < 0.001) as well as a notable increase in the Bacteroidetes (P = 0.008) and Akkermansia (P < 0.001) populations, respectively compare to control group. Mean changes in Lactobacillus populations were marginally significant (P = 0.05). Chitosan administration did not alter the composition in Bifidobacterium populations (P = 0.97). Conclusion The present study demonstrates beneficial effects of chitosan administration on some bacterial species associated with overweight and obesity in adolescents. Further research is needed to confirm our findings and clarify the impact of this intervention on the Lactobacillus population in the gut.